Hypertension and breast cancer risk: a systematic review and meta-analysis - Han, Hedong (Sci Rep, 2017)
Observational studies examining the relationship between hypertension and breast cancer risk have reported conflicting findings. We conducted this systematic review and meta-analysis to summarize the evidence regarding the association between hypertension and risk of breast cancer. Eligible studies were identified through a comprehensive literature search of PubMed, EMBASE, and the Cochrane library until August 2016. We included observational studies that reported relative risks (RR) with corresponding 95% confidence intervals (CIs). Results from individual studies were pooled by using a random-effects model. 29 articles of 30 studies, with totally 11643 cases of breast cancer, were eligible for inclusion in the meta-analysis. We observed a statistically significant association between hypertension and increased breast cancer risk (RR: 1.15; 95% CI: 1.08, 1.22). In the subgroup analysis, we found a positive association between hypertension and breast cancer incidence among postmenopausal women (RR: 1.20; 95% CI: 1.09, 1.31). In contrast, hypertension was not associated with risk of breast cancer among premenopausal women (RR: 0.97; 95% CI: 0.84, 1.12) and Asian population (RR: 1.07; 95% CI: 0.94, 1.22).This meta-analysis collectively suggests a significantly association between hypertension and breast cancer risk, specifically for postmenopausal hypertensive women.